2014
DOI: 10.1371/journal.pone.0112871
|View full text |Cite
|
Sign up to set email alerts
|

Potential Conservation of Circadian Clock Proteins in the phylum Nematoda as Revealed by Bioinformatic Searches

Abstract: Although several circadian rhythms have been described in C. elegans, its molecular clock remains elusive. In this work we employed a novel bioinformatic approach, applying probabilistic methodologies, to search for circadian clock proteins of several of the best studied circadian model organisms of different taxa (Mus musculus, Drosophila melanogaster, Neurospora crassa, Arabidopsis thaliana and Synechoccocus elongatus) in the proteomes of C. elegans and other members of the phylum Nematoda. With this approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 104 publications
(127 reference statements)
0
21
0
Order By: Relevance
“…More importantly, while the 12h rhythms are conserved in C. elegans , homologs of drosophila and mammalian core circadian clock as well as top 24h cycling mouse hepatic genes do not exhibit circadian rhythms under the same conditions (Figures 7D, S7H,I). The lack of circadian oscillation of canonical circadian clock genes in C. elegans have been previously reported in several studies and these genes are believed to play roles in development rather than regulating circadian rhythms in nematodes (Romanowski et al, 2014; van der Linden et al, 2010). Given that the 12h clock is conserved but not the 24h circadian clock between nematodes and mammals, this observation strongly supports our hypothesis that the 12h clock evolved ‘separately’ from the circadian clock and that the mammalian 12h clock is independent from the circadian clock.…”
Section: Resultsmentioning
confidence: 92%
“…More importantly, while the 12h rhythms are conserved in C. elegans , homologs of drosophila and mammalian core circadian clock as well as top 24h cycling mouse hepatic genes do not exhibit circadian rhythms under the same conditions (Figures 7D, S7H,I). The lack of circadian oscillation of canonical circadian clock genes in C. elegans have been previously reported in several studies and these genes are believed to play roles in development rather than regulating circadian rhythms in nematodes (Romanowski et al, 2014; van der Linden et al, 2010). Given that the 12h clock is conserved but not the 24h circadian clock between nematodes and mammals, this observation strongly supports our hypothesis that the 12h clock evolved ‘separately’ from the circadian clock and that the mammalian 12h clock is independent from the circadian clock.…”
Section: Resultsmentioning
confidence: 92%
“…In addition, our bioinformatics analysis showed that KIN-20 has a high degree of homology with its counterpart in arthropods and mammals, with a complete conservation of all regulatory and functional sites (20); thus KIN-20 is a likely target of the PF-670642 selective casein kinase 1e and δ inhibitor. Conservation of the regulatory sites between LIN-42 and PER and between CK1e/δ and KIN-20 suggests the possibility of interactions similar to those found in other species.…”
Section: Discussionmentioning
confidence: 90%
“…A dominant role for CK1-mediated protein phosphorylation in circadian timing has been described in mammals (32), Drosophila melanogaster (33), Neurospora crassa (34), and Ostreococcus tauri (35), even when the putative target proteins of CK1 in their TTFL systems are not conserved. C. elegans has only one protein, encoded by the protein kinase gene kin-20 (20), that is a homolog to the mammalian casein kinases 1e/δ. To test whether PF-670462, a CK1e and δ inhibitor and a common pharmacological modulator of the circadian period in other species, could also influence the sur-5 luminescent rhythms, we recorded the luminescence of single nematodes exposed to different concentrations of the drug.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations